2021
DOI: 10.1021/acs.jchemed.1c00414
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Professional Development on Inclusive Pedagogy Yields Chemistry Curriculum Transformation, Equity Awareness, and Community

Abstract: Persons excluded due to ethnicity or race (PEERs) leave STEM at disproportionate rates; therefore, efforts to engage undergraduate PEERs are critical to creating a diverse STEM workforce. Through a Howard Hughes Medical Institute funded Inclusive Excellence grant (HHMI-IE), the REALISE (REALizing Inclusive Science Excellence) program was developed with the goal to increase student retention and success. As part of this project, an extensive faculty development program, including a backward course design module… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In doing this we would call on learned societies to provide reviews of specific recommendations such as that provided by the Committee for Chemists with Disabilities from the American Chemical Society . Such advice could be built on by also providing templates and examples of risk assessments for example. Institutions provide training around supporting disabled, chronically ill, or neurodivergent students, including training for instructors and teaching assistants . For example, concerning the use of assistance dogs in the laboratory, Ramp et al called for inclusive guidelines for accommodating service dog handlers and raised concerns over “perpetuating negative bias” through the emphasis of “hazards without also emphasizing strategies for hazard minimization and the positive impacts of a more inclusive classroom”.…”
Section: Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In doing this we would call on learned societies to provide reviews of specific recommendations such as that provided by the Committee for Chemists with Disabilities from the American Chemical Society . Such advice could be built on by also providing templates and examples of risk assessments for example. Institutions provide training around supporting disabled, chronically ill, or neurodivergent students, including training for instructors and teaching assistants . For example, concerning the use of assistance dogs in the laboratory, Ramp et al called for inclusive guidelines for accommodating service dog handlers and raised concerns over “perpetuating negative bias” through the emphasis of “hazards without also emphasizing strategies for hazard minimization and the positive impacts of a more inclusive classroom”.…”
Section: Recommendationsmentioning
confidence: 99%
“…50 Such advice could be built on by also providing templates and examples of risk assessments for example. • Institutions provide training around supporting disabled, chronically ill, or neurodivergent students, including training for instructors 51 and teaching assistants. 52 For example, concerning the use of assistance dogs in the laboratory, 53 46,55 This will be achieved by ensuring that chemistry teachers reflect on their learning goals and assessments to be careful that they are not assessing hidden curricula, able-bodiedness, comfort in the learning and assessment environment, culture, belonging and dis-belonging to or in groups etc.…”
Section: Changing Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing and supporting learners concerning EDI, e.g., through (compulsory) training or discussion events, can indeed foster an inclusive culture, but can we then incorporate elements of excellent practice from cultures that are not represented as well as adjust what is already offered? All efforts to identify and address issues concerning EDI and the teaching of the Chemical Sciences are essential.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, literature [13] conducted a study on ICT professional cluster in Gansu Communication Vocational Technology College and concluded that the construction of professional clusters in higher vocational institutions should be combined with the advantageous platforms of local vocational education groups and curriculum clusters to form their educational characteristics. Literature [14] studied professional cluster construction in Suzhou Higher Vocational School as an example and elaborated the construction ideas, objectives, and contents of professional clusters to achieve the goals of professional cluster development and students' professional skills training. The literature [15] found that specialized secondary schools focused on constructing professional clusters and achieved significant results in improving the fit between talent training and market demand and innovation of talent training mode.…”
Section: Introductionmentioning
confidence: 99%